Porta-enxertos e cultivares de mangueira infuenciam o estado nutricional da planta e a fertilidade do solo - Gomes, Fernando Antonio Lima (2023)
Mangifera indica belongs to the Anacardiaceae family, standing out for its potential in fruit growing, considered the sixth most produced fruit in Brazil and the most exported in the country. The high productivity of the mango crop in Brazil is due to the technology applied to the crop, as well as the implantation of orchards through seedlings resulting from the vegetative propagation of the grafting method, which brings greater development and precocity to the plants cultivated in the field, in addition to the program of fertilization that allows greater development and growth both in the seedlings and during the establishment phase of the orchard in the field. In this sense, this study was divided into 3 chapters. Chapter I evaluated the nutritional status of 'Palmer', 'Tommy Atkins', 'Kent' and 'Keitt' mango seedlings grafted on Capucho, Coquinho and Espada polyembryonic rootstocks. Chapter II evaluated the nutritional status of 'Palmer', 'Tommy Atkins', 'Kent' and 'Keitt' mangoes grafted onto polyembryonic rootstocks Capucho, Coquinho and Espada during establishment in dense cultivation in the São Francisco Valley. In Chapter III, the objective was to evaluate the soil fertility of the mango orchard in the establishment phase. The experiment was carried out in two phases, in the fruit nursery of the Campus of Agricultural Sciences of the Federal University of Vale do São Francisco (UNIVASF), in Petrolina-PE and in an experimental orchard of the fruit sector of UNIVASF. Macro, micronutrients and beneficial elements were determined with the following variables Nitrogen (N), Phosphorus (P), Potassium (K), Calcium (Ca), Magnesium (Mg), Zinc (Zn), Copper (Cu), Iron ( Fe), Manganes (Mn), Molybdenum (Mo), Sodium (Na) and Silicon (Si) and considering the fertility of the soil, the variables of Phosphorus (P), Potassium (K), Calcium (Ca), Magnesium ( Mg), Zinc (Zn), Copper (Cu), Iron (Fe), Manganese (Mn), Sodium (Na), Hydrogenion Potential (pH), Electrical Conductivity (EC) Total Acidity (H+Al) and Exchangeable Aluminum ( Al+). The results obtained were submitted to analysis of variance and subsequently to the mean test. The results showed that the leaf contents for the interaction of macronutrients (N, P, K, Ca), micronutrients (Cu and Fe) and silicon (Si) depend on the combination of canopy (Tommy Atkins, Palmer, Keitt and Kent) x door -grafting (Espada, Capucho and Coquinho) in the seedling phase in the nursery; for the establishment phase in the field, determination of the effects of the rootstock on each mango cultivar, three collections of leaves were carried out to evaluate the nutritional status of the plants. Collections were performed at 180, 360, 540 days after transplantation (DAT), which correspond to the months of November 2020 (1st collection), May 2021 (2nd collection) and November 2021 (3rd collection). the leaf contents with 180 DAT, presented interaction for the macronutrients K, Ca and Mg, micronutrients Zn and the beneficial element Na, with 360 DAT prevailed interaction for macronutrients N and Ca, micronutrient (Zn), and at 540 DAT consolidated the interaction macronutrients Ca and Mg, Zn micronutrients, depending on the canopy combination (Tommy Atkins, Palmer, Keitt and Kent) x rootstock (Espada, Capucho and Coquinho); and for the results on soil fertility in the orchard establishment phase in the field with 180 DAT there was interaction for pH and H+Al; already with 360 DAT, significant values prevailed in the interaction for the macronutrient Ca2+, micronutrient Cu2+ and H+Al and in the third collection the interaction for pH was consolidated. EC and H+Al values and P, K, Mg, Zn and Mn contents, regardless of the evaluation date (180, 360, 540 DAT), are independent of canopy cultivars and rootstocks.